What got you here won't get you there in sales! how successful salespeople take it to the next level - Goldsmith, Marshall; Brown, Don 1956-; Hawkins, Bill 1947- (McGraw-Hill, 2012)
The world-renowned leadership expert and bestselling author of What Got You Here Won't Get You There provides what you need to WIN MORE SALES! In What Got You Here Won't Get You There in Sales, Mashall Goldsmith teams up with two leaders in the field of behavioral science--Don Brown and Bill Hawkins--to identify the 16 most common sales habits that damage relationships, then They provide you with good, relationship-building behaviors, such as recruiting stakeholders, looking into the future, and engaging in a follow-up process. Marshall Goldsmith is the author of many bestsellers, including What Got You Here Won't Get You There, Succession, and Mojo. Don Brown is the owner and founder of the training and development company Situational Services, Inc., whose clients include Anheuser-Busch, Dell, Ford, US Airways, and Harley Davidson. Bill Hawkins is a leadership effectiveness consultant whose clients include American Express, AT & T, DirecTV, the IRS, Northrop Grumman, and MGM-Mirage Hotels.
Includes index. - Title from title screen
Keywords: Sales management; Selling; Ventes; Gestion; Vente; selling; Commerce; Business & Economics; Marketing & Sales